Ahab agonistes : the rise and fall of the Omri dynasty - Grabbe, Lester L. (Library of Hebrew Bible/Old Testament studies, 2007)
The European Seminar in Historical Methodology is committed to debating issues surrounding the history of ancient Israel and Judah with the aim of developing methodological principles for writing a history of the period. In this particular session the topic chosen was the Omride dynasty, its rise and fall, and the subsequent Jehu dynasty, down to the fall of Samaria to the Assyrians. Participants discuss such topics as the dating of prophetic texts, the house of Ahab in Chronicles, the Tel Dan inscription, the Mesha inscription, the Jezebel tradition, and the archaeology of Iron IIB.